Pengaruh Penerapan Metode Brainstorming terhadap Hasil Belajar Peserta Didik pada Mata Pelajaran PAI di SMP N 1 Kec. Gunuang Omeh - Celni Navivin; Wedra Aprison (Lembaga Yasin AlSys, 2026)
Although active learning methods have been widely examined in educational research, the effect of the brainstorming method on learning outcomes in Islamic Religious Education (PAI) at the junior high school level, particularly in schools located in non-urban areas, remains relatively underexplored. This study aimed to analyze the effect of the brainstorming method on students’ learning outcomes in the Islamic Religious Education subject at SMP N 1 Gunuang Omeh Subdistrict. A quantitative approach was employed with a quasi-experimental design in the form of a Static Group Comparison Design, involving 40 eighth-grade students selected through total sampling. Data were collected using an objective multiple-choice test and analyzed with the nonparametric Mann–Whitney U test after normality and homogeneity tests were conducted. The results showed a significant difference between the experimental and control groups (p = 0.003 < 0.05), where the experimental group taught using the brainstorming method obtained a mean score of 83.40 with an 85% mastery level, while the control group taught using conventional methods obtained a mean score of 74.10 with a 55% mastery level. These findings reinforce constructivist and social learning theories in the context of Islamic Religious Education and confirm that the implementation of active learning strategies based on brainstorming is effective in improving students’ learning outcomes. The study recommends that Islamic Religious Education teachers further integrate the brainstorming method into classroom practice as part of developing student-centered learning, and encourages subsequent research to examine the impact of this method on affective and psychomotor domains.